Características agronômicas e índices de trocas gasosas de cultivares de tomateiro com diferentes números de hastes por planta - Dalastra, Graciela Maiara (2017)
This work aimed to study the influence of the number of stems per plant in agronomic characteristics and on the gas exchange indexes of two tomato cultivars. The experimental design was of randomized blocks in factorial scheme 2 x 5, with four replicates. The first factor is constituted by two tomatoes cultivars (Giuliana and Tyna) and the second by the number of rods in the plants, being: (1) only the main stem; (2) main stem + secondary stem issued immediately below the first bunch; (3) the first two secondary rods that arise in the plant with the emerge of the main stem; (4) the first four secondary rods that arise in the plant with the emerge of the main stem; (5) main stem and three secondary rods issued below the first bunch. The mean mass, longitudinal and transverse diameter of the fruits evaluated and productivity was estimated. The pH, soluble solids content, titratable acidity and soluble solids / titratable acidity ratio, ascorbic acid content and lycopene were also evaluated. The evaluated characteristics were: liquid assimilations rates of CO2 (A), leaf transpiration (E), stomatal conductance (gs) and inner concentration of CO2 (Ci). From these measures was possible to calculate the instantaneous efficiency of the use of water (EUA) and carboxylation (ACi). The production of Giuliana cultivar war 32% higher than Tyna cultivar. Regarding the types of driving rods there was no difference between the for the characteristics related to the size of the fruit, for the soluble solids the driving type 2 and 3 presented highest values. The lycopene values are considered suitable. In relation of the types of conduction the bigger rates of A was observed to the conduction type 3, although did not resulted in significant differences in the productivity.